An Optimal Solution to an Assignment Problem Using Zero Neighbouring Method (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2019)
Assignment problem is a type of optimization problem which deals with allocation of different  resources to different activities on one-to-one basis. It has a lot of relevance in practical life as  many real world problems are formulated in the form of an assignment problem. In this research  paper, a different approach (other than the existing methods in literature) for solving an assignment  problem has been introduced along with the algorithm and numerical example.
Keywords: Assignment problem; Zero neighbouring method; Hungarian Algorithm; Optimization